Pengaruh Minat Mejadi Guru, Lingkungan Kelaurga, Dan Prospek Lapangan Kerja Terhadap Keputusan Mahasiswa Memilih Program Studi Pendidikan Ekonomi Universitas PGRI Ronggolawe Tuban - Zahrotul Lu'lu'a Hadi Maghfiroh; Ridaul Innayah (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2026)
This study investigated the factors influencing students' decisions to pursue an economics education program. The research focused on the desire to become a teacher, family environment, and career potential. The study employed quantitative and survey methods. Random sampling was used to select a sample of 61 students. The researchers used a Likert-scale questionnaire to collect data and then used multiple linear regression to analyze it. The analysis showed that family environment significantly influenced students' decisions, with a t-value of 2.217 and a significance level of 0.030. Job prospects also showed a significant influence, with a t-value of 2.956 and a significance level of 0.004. With an F-value of 136.726 and a significance level of less than 0.001, all three variables significantly influenced students' decisions. A strong relationship between the study variables is indicated by a correlation coefficient of 0.932. These findings suggest that internal factors and considerations of future employment influence students' decisions.